Estudo dos acidentes com motocicletas e da gravidade das lesões decorrentes - Berger, Pedro Pelacani (2014)
This study seeks to define indicators and identify aggravating factors of traffic accidents involving motorcyclists. Using the database Violence Surveillance System and Accidents (VIVA), from a descriptive cross-sectional study performed on Vitória - ES, in the years 2006, 2007, 2009 and 2011, with victim, route and occurrence information. Analyses were performed in order to define the victim and the accident's profile and use generalized linear models in the investigation of risk and protection factors associated with the severity of the occurrence. The results demonstrate the existence of time interface, day of week, injured body part, occurring in rural or urban area and occurrence municipality belonging to the metropolitan area with the chance of hospitalization and accidents. It was observed that variables with known impact on the quantity of accidents do not necessarily have the same effect on the severity of these, and also highlights the importance of developing a unified, concise and comprehensive information system to build a better understanding of traffic accidents, promoting public policies for road safety in the state.